2020
DOI: 10.1088/1755-1315/537/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, Modification of Artocarpin Compound from Pudau Plant (Artocarpus kemando Miq.) and Bioactivity Antibacterial Assay of Artocarpin Compound and Their Modification Result

Abstract: Artocarpus kemando Miq. is a species from the family Moraceae in Indonesia known as the Pudau plant. The purpose of this study is to isolate, characterize, modify and test the antibacterial activity of artocarpin compounds isolated from pudding plants. Stages of research include sample preparation, extraction, isolation, and purification of compounds using chromatographic techniques (TLC, VLC, and CC), characterization of compounds using spectroscopy. The isolated compound was obtained as a yellow crystal with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Furthermore, the inhibitory effects of cathepsin K have also been described by other workers [22,23]. One of the plants from which flavonoid compounds have been isolated by many workers is A. kemando Miq [13,14,[24][25][26][27], and it has been reported that in many cases, the flavonoids from this plant were found to exhibit positive bioactivity. Another plant reported to contain flavonoids with useful biological activities is Artocarpus.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Furthermore, the inhibitory effects of cathepsin K have also been described by other workers [22,23]. One of the plants from which flavonoid compounds have been isolated by many workers is A. kemando Miq [13,14,[24][25][26][27], and it has been reported that in many cases, the flavonoids from this plant were found to exhibit positive bioactivity. Another plant reported to contain flavonoids with useful biological activities is Artocarpus.…”
mentioning
confidence: 65%
“…The modified artocarpin was confirmed by physical properties, UV-Vis measurement, and FTIR characterization. The compound was also found to exhibit antibacterial activity against Bacillus subtilis and Escherichia coli [25]. As a continuation of the previous study, in this work the modified artocarpin compound was further characterized using NMR and MS techniques, followed by the determination of the anticancer cytotoxicity of the compound against leukemia P-388 cancer cells.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…antibacterial [12], antiplatelet [13], antifungal [14], antimalarial [15], anti-aging [16], and cytotoxic [17].…”
Section: Introductionmentioning
confidence: 99%
“…Artocarpin compounds are flavonoids found in breadfruit plants. Artocarpin is a flavone compound that is often found in Artocarpus plants which contain prenyl groups at C-3 and C-6 [12]. Artocarpin has a hydroxyl group that can undergo oxidation within a certain time, thereby reducing the stability of the compound.…”
Section: Introductionmentioning
confidence: 99%